When eastern and western language systems meet: crossing the English vocabulary threshold versus breaking the Kanji barrier - John Paul Loucky (Penerbit UKM, 2005)
Many lessons can be learned from relevant research in vocabulary- and language-learning strategy training as well as from comparative studies of those learning Oriental languages, which could greatly help language teachers and learners in Kanji-background countries. This article contrasts the minimal threshold levels of vocabulary needed for reading common English text, versus that required for reading basic texts using Kanji characters, whether Chinese, Japanese or Korean. Both mnemonic and Semantic Field Keyword approaches hold great potential for helping such learners from Kanji-block countries by building upon their well-known strengths of rote-memorization, especially of visual images necessary for mastery in reading Kanji-based languages. These areas with a high potential for language learning strategy skill transfer are examined in this study. It compares methods of teaching a Kanji-based language like Japanese to non-natives, with more effective methods for teaching students from Kanji-based countries how to develop better EFL vocabulary and reading skills. Since this is written from an Asian language learners’ perspective, the term “Kanji” will be used in a generic sense to mean Chinese characters or language systems based upon them. When not capitalized, “kanji” will refer to specific use of these characters in Chinese, Japanese or Korean.